2020
DOI: 10.3389/fpsyt.2020.569981
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Physical and Mental Health and Face Mask Use During the COVID-19 Pandemic: A Comparison of Two Countries With Different Views and Practices

Abstract: Background: The physical and mental health of citizens living in a country that encouraged face masks (China) and discouraged face masks (Poland) during the initial stage of the COVID-19 pandemic remained unknown. We conducted a crosscountry study to compare the psychological impact of the COVID-19 pandemic on Poles and Chinese. This study aimed to compare the levels of psychological impact of pandemic and levels of anxiety and depression between China and Poland. Methods: The survey collected information on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
260
3
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(310 citation statements)
references
References 40 publications
(59 reference statements)
19
260
3
2
Order By: Relevance
“…That female's stress was greater than that of males was also consistent with existing evidence [14,16] and similar studies conducted during the pandemic of COVID-19 from different countries [22][23][24][25]. The nding correspondents to epidimeological research suggesting that females have a higher risk of psychological outcomes [35].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That female's stress was greater than that of males was also consistent with existing evidence [14,16] and similar studies conducted during the pandemic of COVID-19 from different countries [22][23][24][25]. The nding correspondents to epidimeological research suggesting that females have a higher risk of psychological outcomes [35].…”
Section: Discussionsupporting
confidence: 87%
“…The nding correspondents to epidimeological research suggesting that females have a higher risk of psychological outcomes [35]. Some researchers have hypothezied that higher psychological stress in females may be partially due to their work being more heavily impacted by COVID-19 and the care burden in home [22,25]. Observed sex differences regarding stress are also often attributed to differential impacts on individuals' social environmental, psychodynamic, and cognitive processes [36,37].…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, as a limitation of this study, this research did not investigate the use of some precautional measures that, according to the current literature, influence psychopathological levels such as hand hygiene and wearing face mask ( Wang et al., 2020a , 2020d ); for example, Wang and colleagues ( Wang et al., 2020a ) demonstrated that there are different habits about using face masks between Chinese and Polish subjects. Specifically, the less frequent use of the face mask by Polish individuals is correlated with higher physical and psychopathological symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…Second, our data also shed light on the fact that professional work context was not associated with STB. This is particularly important because previous reports did suggests that specific features of the working context (such as a shortage of professional equipment [Wang et al., 2020] , disrupted work-life balance [ Gomez et al., 2020 ], or working over hours [Greenberg, 2020] ) were associated with emotional impact. Against this, there are 2 important conclusions for healthcare organizations in prioritizing safe working environments: (a) to improve the identification of STB and current mental disorders (especially depression) in healthcare professionals ( Petrie et al., 2019 ) because our findings suggest that treating current MDE may lead to a reduction of one third of STB cases, and (b) to value the importance of positive social relationships (e.g.…”
Section: Discussionmentioning
confidence: 99%